Media Sosial Sebagai Media Promosi Kewargaan: Studi Etnografi Digital - Arianto, Bambang (Journal of Humanity Studies, 2022)
This research aims to elaborate on the usefulness of social media as a media for citizenship promotion. Dependence on digitalization makes social media increasingly used and influences various civic activities. In the era of the digital economy, the role of social media has become the most important promotional tool for every activity of citizens, business entities and the public. Social media has been used to disseminate various civic activities so that they can then become known to the public. The impact of social media-based civic activities has created dynamic and participatory interaction patterns in promoting activities. This research uses a digital ethnographic approach with in-depth interview techniques and digital participant observation with the millennial generation in Pandeglang Regency, Banten. The research results found that social media has become a media for promoting citizenship, starting from personal activities, business entities and public organizations. Various schemes for strengthening digital civic literacy are needed, so that social media can be well positioned as a media for civic promotion in the era of digitalization.